Challenges Faced by Parents of Children with Learning Disability - George, Jincy Elsy (Journal of Social Work Education and Practice, 2023)
Learning Disability is a neurological disorder and it affects an individual in such way that their brain works differently from others. Hence the processing that occurs in an individual’s brain functions differently in people with Learning Disability. This can cause serious challenge to the individual and family physically, socially and emotionally. The study is of descriptive in nature and describes the various challenges faced by the parents of children with Learning Disability in all these aspects. The study is conducted among 65 parents of children with Learning Disability in Trivandrum.
Keywords: Disability; Learning Disability; Neurological disorder; Children with Disabilities; Parents Challenges